2017
DOI: 10.4274/balkanmedj.2016.0081
|View full text |Cite
|
Sign up to set email alerts
|

The Morphological Anatomy of the Menisci of the Knee Joint in Human Fetuses

Abstract: Background:Development of the foetal period of the meniscus has been reported in different studies.Aims:Evaluation of lateral and medial meniscus development, typing and the relationship of the tibia during the foetal period.Study Design:Anatomical dissection.Methods:We evaluated 210 knee menisci obtained from 105 human foetuses ranging in age from 9 to 40 weeks’ gestation. Foetuses were divided into four groups, and the intra-articular structure was exposed. We subsequently acquired images (Samsung WB 100 26X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The medial meniscus is mainly C-shaped, and various shapes of the medial meniscus have been reported, and morphometry of the medial meniscus is also reported [ 22 , 23 ]. Bloecker et al reported morphometric differences between the medial and lateral menisci by three-dimensional analysis using MRI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The medial meniscus is mainly C-shaped, and various shapes of the medial meniscus have been reported, and morphometry of the medial meniscus is also reported [ 22 , 23 ]. Bloecker et al reported morphometric differences between the medial and lateral menisci by three-dimensional analysis using MRI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discoid menisci were more common than other anomalies, including ring‐shaped LMs, double‐layered LMs, and partially duplicated LMs [1, 6, 12, 15, 35, 38]. Having fundamental embryological knowledge about menisci is critical for the diagnosis and treatment of cases containing various meniscal pathologies [16, 18, 33]. In the early stages of fetal life, both menisci develop into their typical shapes.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated as below: n=(tlα)2(pq)2/S2, where, tl − α : 95% confidence intervals, t value: 1.96. p is incidence of investigated event in the universe (incidence of crescenteric shape of LM was determined as 19% in study of Koyuncu et al [18]), q : 1 − p, S standard error 0.05 for 95% confidence intervals, n is sample number, n = (1.96) 2 (0.19.0.81) 2 /(0.05) 2 : 36.4 (minimum number of individuals).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the study of the morphology and the morphometry of the menisci of the knee joint is invaluable in understanding meniscal anatomy, which is necessary for a clinical diagnosis and the planning of surgical procedures, including arthroscopy and meniscal transplant surgeries (5,6). Several works have already focused on morphological and morphometric examination of the knee menisci of human cadavers, or in vivo through magnetic resonance imaging (6)(7)(8)(9)(10)(11).…”
Section: Emerged Conclusion: Taking Advantage Of Non-invasive Imaging...mentioning
confidence: 99%